2011
DOI: 10.1159/000324545
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Practices among Nursing Staff in Public Secondary Care Hospitals in Kuwait: Self-Report and Direct Observation

Abstract: Objective: To assess the compliance with hand hygiene guidelines among nursing staff in secondary care hospitals in Kuwait. Subjects and Methods: A cross-sectional study was conducted through direct observation using the Lewisham observation tool and self-administered questionnaire in six major public secondary care hospitals in Kuwait. Only patient care activities that are described as ‘dirty contacts’ by the Fulkerson scale were considered as indications for hand hygiene while any attempt for hand hygiene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
9
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 57 publications
(45 reference statements)
11
53
9
3
Order By: Relevance
“…Studies of compliance with hand washing in 2003 at a Saudi hospital showed rates of just 6.7% before patient contact and 23.7% after patient contact (150). Saudi Arabia and Bahrain were among the first countries to sign the Hand Hygiene (151,152). Such suboptimal hand hygiene will invariably contribute to the spread of ␤-lactamase-positive bacteria in the GCC states.…”
Section: Gram-negative Bacilli In the Arabian Peninsulamentioning
confidence: 99%
“…Studies of compliance with hand washing in 2003 at a Saudi hospital showed rates of just 6.7% before patient contact and 23.7% after patient contact (150). Saudi Arabia and Bahrain were among the first countries to sign the Hand Hygiene (151,152). Such suboptimal hand hygiene will invariably contribute to the spread of ␤-lactamase-positive bacteria in the GCC states.…”
Section: Gram-negative Bacilli In the Arabian Peninsulamentioning
confidence: 99%
“…Moreover, some laboratory personnel in Lebanon lacked proper knowledge and practice about how to dispose blood-contaminated waste [13]. In Kuwait, hand hygiene compliance among nursing staff in secondary care hospitals had been reported to be poor [14]. …”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study conducted by direct observation using the Lewisham observation tool and self-administered questionnaire in six major public Science Publications AJID secondary care hospitals in Kuwait resulted in an overall compliance increase of 33.4% after staff training (Al-Wazzan et al, 2011). Compliance rates significantly varied between different ward categories from 14 in emergency to 55% in medical wards.…”
Section: Resultsmentioning
confidence: 99%
“…Being busy with work (42.2%), having sore/dry hands (30.4%) and wearing gloves (20.3%) were the most frequently reported hindrances to improving hand hygiene in that study. Only patient care activities that are described as 'dirty contacts' by the Fulkerson scale were considered as indications for hand hygiene while any attempt for hand hygiene was considered as compliance (Al-Wazzan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%